2021
DOI: 10.1177/00048674211025697
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and treatment outcome of suicidal depression: Two large naturalistic cohorts of depressed outpatients

Abstract: Objective: The emergence of new drugs for managing suicidal ideation (e.g. ketamine) raises the question of whether suicidal depression (i.e. moderate to severe depression with concomitant suicidal ideation) is a specific depression phenotype. Therefore, this study characterized patients with suicidal depression (baseline clinical characteristics, suicidal ideation and depression evolutions, suicide risk) in two large cohorts of outpatients with depression. Methods: LUEUR and GENESE are two large, prospective,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…Indeed, patients with suicidal depression have more severe baseline clinical features, respond less well to antidepressants, may have a different clinical course (e.g., depression remission) and have higher suicidal risk than depressed patients without SI [21][22][23][24][25]. We previously reported similar results in a study on two large cohorts of outpatients with unipolar depression [24].…”
Section: Introductionsupporting
confidence: 57%
“…Indeed, patients with suicidal depression have more severe baseline clinical features, respond less well to antidepressants, may have a different clinical course (e.g., depression remission) and have higher suicidal risk than depressed patients without SI [21][22][23][24][25]. We previously reported similar results in a study on two large cohorts of outpatients with unipolar depression [24].…”
Section: Introductionsupporting
confidence: 57%
“…8 Growing evidence suggests that suicidal depression (ie, depression with SI) could be a specific phenotype of depression. Compared with depressed patients without SI, suicidal depressed patients are characterized by more severe clinical features (eg, greater depressive symptom severity and number of depressive episodes, more frequent history of SA) [9][10][11] and worse response to antidepressant treatment. They are also less likely to achieve remission.…”
Section: Introductionmentioning
confidence: 99%
“…16 Indeed, depressive symptomatology profiles are different in patients with and without SI. 10,17,18 The opioid system might be involved in SB physiopathology. 19 It has been shown that consumption of opiate analgesics is higher in patients with suicidal depression than in those without suicidal depression and in healthy controls, independently of their health status.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations